2007
DOI: 10.5458/jag.54.109
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Glucanotransferase that Produces a Cyclomaltopentaose Cyclized by an .ALPHA.-1,6-Linkage

Abstract: Enzymatic syntheses of various nonreducing oligosaccharides from starch have been reported by many researchers. Nonreducing oligosaccharides are generally divided into two groups: linear and cyclic oligosaccharides. Trehalose (α D glucopyranosyl α D glucopyranoside) is a typical linear nonreducing oligosaccharide occurring in bacteria, yeasts, fungi, plants, and invertebrates. Mass production of trehalose from starch has been developed using two bacterial enzymes, maltooligosyltrehalose synthase (EC 5.4.99.15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The enzyme activity of IgtY (ICG5-forming activity) was assayed as described in a previous paper. 11) The activity of IgtZ was assayed as follows:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzyme activity of IgtY (ICG5-forming activity) was assayed as described in a previous paper. 11) The activity of IgtZ was assayed as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Our previous report showed that the novel glucanotransferase, isocyclomaltooligosaccharide glucanotransferase (IgtY), converted -1,4-glucan into ICG5 and ICG6 by a one-step reaction. 11) We now report the 8,325-bp sequence of the genomic DNA from B. circulans AM7, which contains igtY and two open reading frames (ORFs). We also report the amino-acid sequences deduced from igtY and the ORFs.…”
mentioning
confidence: 99%
“…The activities of IGTase and CGTase were assayed as reported in previous publications. 13,14) Isoamylase (EC 3.2.1.68) from Pseudomonas amylodelamosa was prepared in our laboratories. The activity of isoamylase was assayed as reported in a previous publication.…”
Section: Methodsmentioning
confidence: 99%
“…1). 13) In this study, we report on the reaction conditions y To whom correspondence should be addressed. Tel: +81-86-276-3142; Fax: +81-86-276-8670; E-mail: h-watanabe@hayashibara.co.jp required for the production of ICG5 from starch using IGTase.…”
Section: !6)-maltose (Cmm) Cyclo-{!6)--dglc P-(1!4)--d-glc P-(1!6)-mentioning
confidence: 99%
See 1 more Smart Citation